2022
DOI: 10.3389/fmicb.2022.883650
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota Characteristics Are Associated With Severity of Acute Radiation-Induced Esophagitis

Abstract: BackgroundAcute radiation-induced esophagitis (ARIE) is one of the most debilitating complications in patients who receive thoracic radiotherapy, especially those with esophageal cancer (EC). There is little known about the impact of the characteristics of gut microbiota on the initiation and severity of ARIE.Materials and MethodsGut microbiota samples of EC patients undergoing radiotherapy (n = 7) or concurrent chemoradiotherapy (n = 42) were collected at the start, middle, and end of the radiotherapy regimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 55 publications
1
6
0
Order By: Relevance
“…Oral microorganisms can cause esophageal cancer by inducing mild chronic inflammation and distal esophageal cancer [ 24 ]. The characteristics of the gut microbiome affect the severity of acute radiation-induced esophagitis [ 25 ]. Interestingly, the microbiome was more abundant in patients with leukemia undergoing radiotherapy with milder gastrointestinal dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oral microorganisms can cause esophageal cancer by inducing mild chronic inflammation and distal esophageal cancer [ 24 ]. The characteristics of the gut microbiome affect the severity of acute radiation-induced esophagitis [ 25 ]. Interestingly, the microbiome was more abundant in patients with leukemia undergoing radiotherapy with milder gastrointestinal dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Dendritic cell antigen presentation was modulated by the gut microbiota via a radiotherapy-induced antitumor immune response (CD8+). Vancomycin potentiated the radiotherapy-induced antitumor immune response and tumor growth inhibition dependent on cytolytic CD8+ T cell/IFNγ elicitation and the abscopal effect [ 25 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The genus Veillonella includes gram-negative, anaerobic, non-motile, and non-spore-forming coccus bacteria ( Djais et al, 2019 ). Veillonella is strongly associated with the development of several diseases, and has been found to promote the proliferation of lung adenocarcinoma ( Zeng et al, 2023 ), whilst Veillonella activates macrophages to promote inflammatory responses via the LPS-TLR4 pathway ( Zhan et al, 2022 ), for example, Veillonella correlated with the severity of radiation esophagitis ( Lin et al, 2022 ), and inflammation is one of the factors leading to esophageal cancer, suggesting that Veillonella may indirectly contribute to esophageal carcinogenesis through inflammation. In our study, only the genus Veillonella positively correlated with ESCA.…”
Section: Discussionmentioning
confidence: 99%
“…Further, significant variations have been reported in the composition and abundance of fecal microorganisms between patients with ESCA and healthy controls. Notably, these differences are closely correlated with the severity of the disease, suggesting that the gut microbiota may play a significant role in the development of ESCA ( Li et al, 2022 ; Lin et al, 2022 ). Moreover, gut microbiota can alter genome-wide methylation levels in ESCA, which may be one of the mechanisms influencing the malignant behavior of ESCA cells ( Baba et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…An increasing corpus of studies has demonstrated the intricate relationships between ESCA and the human gut ora in recent years [18][19][20][21]. The composition and abundance of fecal microorganisms in ESCA patients are closely related to the severity of the disease [22]. In addition, the genome-wide methylation level of ESCA can be regulated by the gut microbiota, which affects the occurrence, development, and metastasis of ESCA.…”
Section: Introductionmentioning
confidence: 99%